The Flexing Phenomenon on Social Media Is Between Educating and Showing Off in Criminal Law Aspects - Merry Lenda Kumajas; Henry N. Lumenta; Paulus Robert Tuerah; Hendrasari Rawung; Romi Mesra (Labor Program Studi Pendidikan Sosiologi, 2024)
This study aims to investigate the flexing phenomenon on social media, exploring its position between financial education and ostentatious displays of wealth, with a focus on its implications in criminal law aspects in Indonesia. The research employed a qualitative methodology, utilizing interviews with key stakeholders, focus group discussions, analysis of social media content, and a comprehensive literature review. Additionally, the study incorporated comparative analysis with other Southeast Asian countries to provide regional context. The results reveal a complex interplay of social, legal, and educational factors surrounding the flexing phenomenon. Key findings include: (1) a significant divergence in perceptions of flexing among different stakeholders, with influencers viewing it as inspirational while legal experts express concerns about potential legal scrutiny; (2) the effectiveness of flexing as an educational tool when balancing success stories with practical financial advice; (3) a notable knowledge gap among social media users regarding the legal implications of their online behavior; (4) growing concerns about the use of social media evidence in financial crime investigations; (5) the emergence of